2019
DOI: 10.2478/izajolp-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Overeducation in Europe: The Role of Field of Study

Abstract: This study investigates the incidence of overeducation among graduate workers in 21 European Union countries and its underlying factors based on the European Labor Force Survey 2016. Although controlling for a wide range of covariates, the particular interest lies in the role of fields of study for vertical educational mismatch. The study reveals country differences in the impact of these factors. Compared to Social sciences, male graduates from, for example, Education, Health and welfare, Engineering, and ICT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 48 publications
(60 reference statements)
1
10
0
3
Order By: Relevance
“…Previous overeducation research considering educational fields focused on higher education, whereas differences across levels of education (vocational and academic) have not been analyzed so far. For the case of academic education, single-country and multiplecountry studies have confirmed cross-field differences in the overeducation risks of graduates in Germany (Berlingieri and Erdsiek 2012;Berlingieri and Zierahn 2014;Ortiz and Kucel 2008;Rossen et al 2019). The empirical evidence supports the importance of higher education differentiation in the form of field of study for understanding overeducation risks (Barone and Ortiz 2011;Ortiz and Kucel 2008).…”
Section: Overeducation Across Educational Fieldsmentioning
confidence: 62%
See 3 more Smart Citations
“…Previous overeducation research considering educational fields focused on higher education, whereas differences across levels of education (vocational and academic) have not been analyzed so far. For the case of academic education, single-country and multiplecountry studies have confirmed cross-field differences in the overeducation risks of graduates in Germany (Berlingieri and Erdsiek 2012;Berlingieri and Zierahn 2014;Ortiz and Kucel 2008;Rossen et al 2019). The empirical evidence supports the importance of higher education differentiation in the form of field of study for understanding overeducation risks (Barone and Ortiz 2011;Ortiz and Kucel 2008).…”
Section: Overeducation Across Educational Fieldsmentioning
confidence: 62%
“…Occupation-specific fields should more likely lead to a homogeneous assessment of skills and abilities relevant for the occupation than less specific, more general fields of education. More occupationally specific fields of education seem to represent entry requirements for the corresponding occupations that are generally acknowledged by employers (Rossen et al 2019). Employers may thereby more easily make assumptions about skills relevant for the job, without relying on additional information on personal and non-cognitive characteristics (Capsada-Munsech 2015).…”
Section: Hypothesis 4b (H4b)mentioning
confidence: 99%
See 2 more Smart Citations
“…В статье F. Green и S. McIntosh с использованием данных по Великобритании наиболее высокие показатели недоиспользования образования выявлены для лиц с дипломами в сфере управления, бизнеса и социальных наук, наиболее низкие -в сфере информационных технологий и естественных наук [23]. В статье A. Rossen и соавторов, анализирующих данные по 21 стране Евросоюза, более высокие показатели недоиспользования образования получены для специалистов с дипломами в сфере услуг и в области естественных наук, более низкие -для инженеров, специалистов в области педагогики, медицины, информационных технологий [24]. В статье J. Robst наиболее высокие показатели недоиспользования в США отмечены для работников с дипломами в сфере социальных наук, филологии и многопрофильных программ (Liberal Arts); наиболее низкие -у работников с дипломами в сфере информационных технологий, медицины и библиотечного дела [25].…”
unclassified